1998
DOI: 10.1523/jneurosci.18-21-08965.1998
|View full text |Cite
|
Sign up to set email alerts
|

Task-Dependent Viscoelasticity of Human Multijoint Arm and Its Spatial Characteristics for Interaction with Environments

Abstract: Human arm viscoelasticity is important in stabilizing posture, movement, and in interacting with objects. Viscoelastic spatial characteristics are usually indexed by the size, shape, and orientation of a hand stiffness ellipse. It is well known that arm posture is a dominant factor in determining the properties of the stiffness ellipse. However, it is still unclear how much joint stiffness can change under different conditions, and the effects of that change on the spatial characteristics of hand stiffness are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
270
4
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(291 citation statements)
references
References 34 publications
16
270
4
1
Order By: Relevance
“…Indeed, the K ilf values derived in this study were in the lower region of the wide range of total joint stiffness values (14-126 N m·rad −1 ) reported in the literature (e.g. Bennet et al 1992;Lacquaniti et al 1993;Gomi and Osu 1998). The large variation of stiffness values supports the claim of Latash and Zatsiorsky (1993) that neither the definition nor the experimental determination of stiffness is without problems.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Indeed, the K ilf values derived in this study were in the lower region of the wide range of total joint stiffness values (14-126 N m·rad −1 ) reported in the literature (e.g. Bennet et al 1992;Lacquaniti et al 1993;Gomi and Osu 1998). The large variation of stiffness values supports the claim of Latash and Zatsiorsky (1993) that neither the definition nor the experimental determination of stiffness is without problems.…”
Section: Discussionsupporting
confidence: 63%
“…The large variation of stiffness values supports the claim of Latash and Zatsiorsky (1993) that neither the definition nor the experimental determination of stiffness is without problems. In particular, Gomi et al (Gomi and Kawato 1997;Gomi and Osu 1998) suggested that the large variation in reported stiffness values is related to differences in experimental setup and instructions. As one example, in the study of Lacquaniti et al (1982), in which stiffness values up to 126 N m·rad −1 were reported, subjects were instructed to maximally resist a deterministic perturbation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous reports have estimated human arm impedance during multi-joint voluntary movements (Gomi and Kawato 1997;Gomi and Osu 1998;Dolan et al 1993;Lacquaniti et al 1993). In these works, small perturbations were applied to the limb and the restoring forces were approximated as a function of displacement.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have examined muscle co-contraction in single joint movement in the context of unstable mechanical loads (e.g., De Serres and Milner 1991;Milner 2002a). In work on two-joint movement, evidence that subjects can alter the pattern of arm impedance has been reported in studies that have assessed stiffness during movement (Burdet et al 2001; and in studies in which the limb is stationary but when the subject is actively applying force Gomi and Osu 1998;McIntyre et al 1996;Perreault et al 2002). However, in the two-joint arm, little is known about the control of impedance when the limb is stationary and net force output is zero.…”
Section: Introductionmentioning
confidence: 99%